Noninvasive beat‐to‐beat finger arterial pressure monitoring during orthostasis: a comprehensive review of normal and abnormal responses at different ages. (10th July 2017) - van Wijnen, V. K.; Finucane, C.; Harms, M. P. M.; Nolan, H.; Freeman, R. L.; Westerhof, B. E.; Kenny, R. A.; ter Maaten, J. C.; Wieling, W.
Abstract: Over the past 30 years, noninvasive beat‐to‐beat blood pressure (BP) monitoring has provided great insight into cardiovascular autonomic regulation during standing. Although traditional sphygmomanometric measurement of BP may be sufficient for detection of sustained orthostatic hypotension, it fails to capture the complexity of the underlying dynamic BP and heart rate responses. With the emerging use of noninvasive beat‐to‐beat BP monitoring for the assessment of orthostatic BP control in clinical and population studies, various definitions for abnormal orthostatic BP patterns have been used. Here, age‐related changes in cardiovascular control in healthy subjects will be reviewed to define the spectrum of the most important abnormal orthostatic BP patterns within the first 180 s of standing. Abnormal orthostatic BP responses can be defined as initial orthostatic hypotension (a transient systolic BP fall of >40 mmHg within 15 s of standing), delayed BP recovery (an inability of systolic BP to recover to a value of >20 mmHg below baseline at 30 s after standing) and sustained orthostatic hypotension (a sustained decline in systolic BP of ≥20 mmHg occurring 60–180 s after standing). In the evaluation of patients with light‐headedness, pre(syncope), (unexplained) falls or suspected autonomic dysfunction, it is essential to distinguish between normal cardiovascular autonomic regulation and these abnormal orthostatic BP responses. The prevalence, clinical relevance and underlying pathophysiological mechanisms of these patterns differ significantly across the lifespan. Initial orthostatic hypotension is important for identifying causes of syncope in younger adults, whereas delayed BP recovery and sustained orthostatic hypotension are essential for evaluating the risk of falls in older adults.